L-mimosine and hypoxia can increase angiogenin production in dental pulp-derived cells - Klara Janjić; Michael Edelmayer; Andreas Moritz; Hermann Agis (BMC, 2017)
Abstract Background Angiogenin is a key molecule in the healing process which has been successfully applied in the field of regenerative medicine. The role of angiogenin in dental pulp regeneration is unclear. Here we aimed to reveal the impact of the hypoxia mimetic agent L-mimosine (L-MIM) and hypoxia on angiogenin in the dental pulp. Methods Human dental pulp-derived cells (DPC) were cultured in monolayer and spheroid cultures and treated with L-MIM or hypoxia. In addition, tooth slice organ cultures were applied to mimic the pulp-dentin complex. We measured angiogenin mRNA and protein levels using qPCR and ELISA, respectively. Inhibitor studies with echinomycin were performed to reveal the role of hypoxia-inducible factor (HIF)-1 signaling. Results Both, L-MIM and hypoxia increased the production of angiogenin at the protein level in monolayer cultures of DPC, while the increase at the mRNA level did not reach the level of significance. The increase of angiogenin in response to treatment with L-MIM or hypoxia was reduced by echinomycin. In spheroid cultures, L-MIM increased angiogenin at protein levels while the effect of hypoxia was not significant. Angiogenin was also expressed and released in tooth slice organ cultures under normoxic and hypoxic conditions and in the presence of L-MIM. Conclusions L-MIM and hypoxia modulate production of angiogenin via HIF-1 differentially and the response depends on the culture model. Given the role of angiogenin in regeneration the here presented results are of high relevance for pre-conditioning approaches for cell therapy and tissue engineering in the field of regenerative endodontics.